TRANFORMASI DIGITAL DALAM ADMINISTRASI PAJAK DAERAH: ANALISIS EFISIENSI PELAYANAN DAN KEPATUHAN WAJIB PAJAK - Loso Judijanto; Al-Amin (ADMIN: Jurnal Administrasi Negara, 2026)
Digital transformation in local tax administration has revolutionised public service efficiency and taxpayer compliance through the implementation of the e-SPTPD system, e-SPPT PBB-P2, and QRIS-based payment applications such as ‘Ayo Balapan’ in various local governments in Indonesia. The research method used in this study was a literature review. The results confirm that digitalisation forms inclusive data-driven fiscal governance, with recommendations for a 2026-2030 national masterplan to achieve a PAD/APBD ratio of 15% through the synergy of technology, human resources, and regulations.